2009
DOI: 10.1124/dmd.109.028274
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition and Induction of Human Liver Cytochrome P450 Enzymes by Milnacipran

Abstract: ABSTRACT:Milnacipran (Savella) inhibits both norepinephrine and serotonin reuptake and is distinguished by a nearly 3-fold greater potency in inhibiting norepinephrine reuptake in vitro compared with serotonin. We evaluated the ability of milnacipran to inhibit and induce human cytochrome P450 enzymes in vitro. In human liver microsomes, milnacipran did not inhibit CYP1A2, 2B6, 2C8, 2C9, 2C19, or 2D6 (IC 50 > 100 M); whereas, a comparator with dual reuptake properties [duloxetine (Cymbalta)] inhibited CYP2D6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 30 publications
3
65
0
Order By: Relevance
“…According to the model, the induction of the hydroxylation of BRV to BRV-OH accounts for the observed decrease in the acid BRV-AC formation. The higher induction effect of rifampin on the CYP2C19-mediated reaction over CYP2C9 is consistent with previous in vitro hepatocyte data (Raucy et al, 2002;Madan et al, 2003;Paris et al, 2009), as well as reported clinical interaction studies (Inui et al, 2013). Of interest, when tested in vitro, rifampin induces both CYP2C9 and CYP2C19 mRNA, with a somewhat larger effect on the former (Yajima et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…According to the model, the induction of the hydroxylation of BRV to BRV-OH accounts for the observed decrease in the acid BRV-AC formation. The higher induction effect of rifampin on the CYP2C19-mediated reaction over CYP2C9 is consistent with previous in vitro hepatocyte data (Raucy et al, 2002;Madan et al, 2003;Paris et al, 2009), as well as reported clinical interaction studies (Inui et al, 2013). Of interest, when tested in vitro, rifampin induces both CYP2C9 and CYP2C19 mRNA, with a somewhat larger effect on the former (Yajima et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Recombinant (high-reductase) CYP3A4 + b 5 and CYP3A5 + b 5 were purchased from Cypex (Dundee, Scotland) or BD Gentest (Woburn, MA). The sources of all other reagents have been described elsewhere (Paris et al, 2009;Parkinson et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…AB Sciex API2000 or 3000 triple quadrupole mass spectrometers in positive mode with ESI and MRM scanning were used for analyte detection. Methods are described in more detail elsewhere (Paris et al, 2009). For all other P450 substrates, analysis was conducted as described previously .…”
Section: Methodsmentioning
confidence: 99%